Cathodic and Anodic Stress Corrosion Cracking of a New High-Strength CrNiMnMoN Austenitic Stainless Steel - Mathias Truschner; Jacqueline Deutsch; Gregor Mori; Andreas Keplinger (Metals, 2020)
A new high-nitrogen austenitic stainless steel with excellent mechanical properties was tested for its resistance to stress corrosion cracking. The new conventional produced hybrid CrNiMnMoN stainless steel combines the excellent mechanical properties of CrMnN stainless steels with the good corrosion properties of CrNiMo stainless steels. Possible applications of such a high-strength material are wires in maritime environments. In principle, the material can come into direct contact with high chloride solutions as well as low pH containing media. The resistance against chloride-induced stress corrosion cracking was determined by slow strain rate tests and constant load tests in different chloride-containing solutions at elevated temperatures. Resistance to hydrogen-induced stress corrosion cracking was investigated by precharging and ongoing in-situ hydrogen charging in both slow strain rate test and constant load test. The hydrogen charging was carried out by cathodic charging in 3.5 wt.% NaCl solution with addition of 1 g/L thiourea as corrosion inhibitor and recombination inhibitor to ensure hydrogen absorption with negligible corrosive attack. Slow strain rate tests only lead to hydrogen induced stress corrosion cracking by in-situ charging, which leads to total hydrogen contents of more than 10 wt.-ppm and not by precharging alone. Excellent resistance to chloride-induced stress corrosion cracking in 43 wt.% CaCl2 at 120 °C and in 5 wt.% NaCl buffered pH 3.5 solution at 80 °C is obtained for the investigated austenitic stainless steel.